Análise experimental e numérica da fluidização para aplicações industriais - LOURENÇO, Reimar de Oliveira (Universidade Federal do Pará, 2017)
The gas-particle fluidized beds have great importance in the processing industry, due to have a good effect of mixing between the phases, and high rates of heat and mass transfer, requiring it to lower power consumption. Some typical examples of industrial applications of this equipment can be found in processes involving catalytic reactions, catalyst regeneration, or the combustion and coal of gasification. The understanding of the fluid dynamic behavior of this equipment is of fundamental importance for the fluidized bed can be adapted to new conditions. The literature reports several studies of fluidized bed, reporting varied contributions already incorporated the knowledge of the operation. The CFD (Computational Fluid Dynamics) tool has proved a good alternative for understanding the operation of this equipment. The use of multiphase granular Eulerian model together with the conservation equations of mass, energy and momentum for each of the phases present, has shown success when applied to fluidized beds. Overall, this work is to study the behavior of the fluid dynamic flow of glass beads and alumina in conventional fluidized bed type gas-solid, varying models Gidaspow, Syamlal-O’Brien and Wen-Yu, as well as Turbulence Models K-ε and RSM. More specifically, the work seeks to study the behavior of the fluid-dynamic equipment, by monitoring the most important fluid-dynamic parameters, among which we highlight the minimum fluidization velocity of the same, the pressure drop at minimum fluidization equipment, its porosity and expansion of the bed particles, also at minimum fluidization. Experimental tests were compared with numerical simulations using CFD (Computational Fluid Dynamics) tool, in which good agreement of the simulated results compared to experimental results.